Estomatitis subprotésica en pacientes con enfermedades sistémicas - Damaris Ximena, Yerbabuena Guaman (2022)
ABSTRACT The present investigation was established in the need to recognize some manifestations and considerations in the dental management of patients who use dental prostheses who may be compromised by systemic pathologies that, although they may be under control, others may go unnoticed by the dental professional who assists them. , leading this research to focus on determining the relationship of subprosthetic stomatitis in patients with systemic disease, its characterization in dental practice, and the identification of the main systemic diseases that affect users of dental prostheses, through a bibliographic review of studies Highly relevant scientists carried out in the last 20 years with respect to subprosthetic stomatitis and systemic diseases. The exhaustive bibliographic analysis led to the conclusion that there are areas such as the use of dental prostheses (adaptation, manufacturing, hygiene, continuous use), alterations in the oral mucosa, the aging process in the oral cavity, the diverse use of medications, the widespread use of antifungals, to which dental professionals must pay considerable interest due to their notoriety in the context of the study, which adds to the particular characteristics of subprosthetic stomatitis, being commonly asymptomatic and multifactorial. The study concluded that cardiovascular disease, pneumonia, diabetes and chronic obstructive pulmonary disease are systemic diseases that affect the oral health of patients with dental prostheses, due to the high bibliographic content evidenced in this study, in parallel, gastrointestinal diseases. , blood or respiratory tract are not relevant to reaffirm themselves as systemic diseases that affect the oral health of patients with dental prostheses. Keywords: subprosthetic stomatitis, patients with systemic disease, systemic diseases, dental prostheses, dental diseases Reviewed by: Mgs. Sonia Granizo Lara. English professor. c.c.0602088890